ANALISIS PENGARUH JUMLAH OBYEK WISATA,JUMLAH WISATAWAN DAN PENDAPATAN PERKAPITA TERHADAP PENDAPATAN RETRIBUSI OBYEK PARIWISATA 35 KABUPATEN/KOTA DI JAWA TENGAH - Ferry Pleanggra; Edy Yusuf A.G (Diponegoro Journal of Economics, 2012)
ABSTRACT One of the indicators used to determine the impact of tourism on the economy of the region, and also as one of the deciding factors for high rates of economic growth of revenue areas is through tourism object is received. Where this certainly describes the situation good economy where every tourist trip will certainly be beneficial to the economy of a region on the visit. From this common saying that the condition of the economy in Central Java is good enough. And imposes to GDP which certainly will also increase. This research aims to (i) Analyze the factors that influenced the development of the income levy tour destinations in 35 counties/cities of Central Java region; (ii) analyzing the factors that most affect the revenue development of tourist objects in 35 levy kabupaten/kota region of Central Java. The purpose of this research is accomplished by a method of Analysis Models used are data with Fixed approaches penel Effect Model (FEM) or Least Square Dummy Variable (LSDV) model, using data time series for five years (2006-2010) and data cross section as much as 35 county/city in Central Java. The LSDV model can get results estimates expected a more efficient. This is due to the high number of observations that have implications on data that is more informative, more varied, and the increased degree of freedom (df). From analysis in mind that variable number of objects of tourism, the number of tourists and income per capita impact positively and significantly to revenue retribution in tourism object 35 counties/cities of Central Java.